In-silico Design of Novel Prazosin Analogues in the Treatment of Hypertension - Sahu, Sunil; Jain, Sanmati K. (Challenges and Advances in Pharmaceutical Research Vol. 7, 2022)
Prazosin is a \(α\)1-adrenoceptor antagonistic drug used to treat high blood pressure (hypertension). In the present study, newer Prazosin analogues were generated using bioisosteric approach. MolOpt, a web server for in silico drug design was used replacing aminoqunazoline group of the Prazosin resulting in 190 bioisosteres. Pharmacokinetic (absorption, distribution, metabolism and excretion) and toxicity properties were calculated by using ADMETlab 2.0. Results displays that analogue 046 (Hexahydrofuro[3,2-b]furan), 182 (1,3-Oxazolidine) and 187 (Pyrido[3,4-b]Pyrazine)] reveal lower human ether-a-go-go-related gene (hERG) levels (less cardiotoxic), less human hepatotoxicity (H-HT) and less drug induced liver injury (DILI) demonstrating lower toxicity as compared to Prazosin. Drug-likeness and drug score was also computed and quantitative estimate of drug-likeness (QED) value was found to be \(\ge\) 0.67. Other analogues were also more active and less toxic than the standard drug. This study will take the lead to the development of novel \(α\)1-adrenoceptor antagonists for the treatment of hypertension.